An InGaAsSb Based 640 × 512 Focal Plane Array With Low Surface Leakage Current for Extended Shortwave Detection - Xie, Ruoyu; Shan, Yifan; Yao, Lingze; Wu, Donghai; Su, Xiangbin; Hao, Hongyue; Jiang, Dongwei; Yang, Mengqi; Zhang, Ye; Xie, Hui; Wang, Guowei; Xu, Yingqiang; et al. (IEEE photonics journal, 2025)
An extended-wavelength InGaAsSb focal plane array (FPA) with a 15 μm pixel pitch, 640 × 512 format, and a cutoff wavelength of 3.22 μm is demonstrated. Through the atomic layer deposition Al 2 O 3 passivation technology, the natural oxide leakage channel is reduced and the leakage current of the device is well suppressed. The optoelectronic performance of the FPA is close to that of the large-scale test unit. At 180 K, the quantum efficiency of the FPA is 45.6% and the dark current is about 2.76 × 10 −5 A/cm 2 . Laboratory imaging shows potential for applications at temperatures above 200 K.